Phytoplankton assemblages and photosynthetic pigments during winter and spring in the Subtropical Convergence region near New Zealand - F. Hoe Chang; Mark Gall (New Zealand Journal of Marine and Freshwater Research, 1998)
The distribution of phytoplankton on both the east, in the region near the Subtropical Convergence (STC), and the west coast of South Island, New Zealand was investigated in winter and spring 1993. Water samples were analysed for the cell carbon biomass, species composition, and pigment characteristics. In both winter and spring, the overall biomass/standing stocks consistently were greatest in the STC, intermediate in the subtropical (ST) both on the west (ST(W)) and east (ST(E)) coasts, and the least in the subantarctic (SA) waters. In spring, organic cell carbon and chlorophyll a measured in the STC were up to 6‐fold greater than in winter. In the STC in both seasons, phytoplankton assemblages were dominated by diatoms, and these species were more similar to those found in ST than in SA waters. The domination of diatoms in phytoplankton assemblages in the STC is consistent with the predominance of fucoxanthin observed in this region. The highest diatom concentrations (both in terms of cell carbon and chlorophyll a ) detected during the spring bloom in the STC were located either at 10 m below the surface, or below the euphotic zone (close to the bottom of mixed layer depth). The most abundant diatom species recorded in both winter and spring in the STC were Lauderia annulata and Nitzschia/Pseudo‐nitzschia spp. In ST waters dinoflagellates and diatoms were dominant in winter and spring respectively. To the south in both winter and spring, however, small‐celled nanoflagellates were dominant in the high nutrient and low chlorophyll (HNLC) SA waters. The domination of nanoflagellates in SA waters in both seasons corresponded well with the predominance of indicative pigments (viz., 19'‐hexanoyl‐oxyfucoxanthin, 19'‐butanoyloxyfucoxanthin, and diadinoxanthin). The generally shallower, nutrient‐rich (NO 3 ‐ , 5–12 (imol litre ‐1 ) waters over Chatham Rise in the STC provides a relatively stable water column, and is suggested to support high abundance of diatoms. Low concentrations of dissolved reactive silicate (DRSi) and the build‐up of diatoms observed in the STC in spring implied DRSi limitation.